Choose Health LA MOMs: A Novel Approach to Postpartum Weight Loss [17I]. (May 2016) - Ramos, Diana; Lopez, Leslie; Resser, Lonnie; Rodriguez, Nancy; Donatoni, Giannina
Abstract : INTRODUCTION: In the U.S., 2 in 3 reproductive age women are overweight or obese. Although weight gain is normal during pregnancy, only 37% of moms return to their pre-pregnancy weight by 6 months postpartum. Weight loss initiatives for postpartum women have been limited. CH LA MOMs, six-month self-initiated program, fills this gap. Enrollment starts in the hospital. The program centers on three core activities-breastfeeding, drinking water and walking and assess the social determinants of health (SDH) affecting the mom. CH LA MOMs is delivered via text messages and e-lessons. METHODS: 46 post-partum women of various economic levels and ethnicities were enrolled. Participants completed a baseline questionnaire assessing SDH. Text messages were sent three times a week reinforcing the core components along with a link to short lessons Progress trackers and award badges were given for goals achieved. Progress was recorded via monthly surveys. Quantitative and qualitative data were analyzed. RESULTS: Results: 67% had a vaginal delivery and 32% a c-section.65% gained more than 25 lb during pregnancy. 48.7% reached their pre-pregnancy weight by 8 weeks postpartum. Among overweight and obese moms 91% reported at least one SDH (60% income and 40% depression and anxiety). Breast feeding was the initiative adopted the least −56%. Water consumption was adopted the most −80.5%. CONCLUSION: CH LA MOMs has the potential to transform the delivery and outcomes of postpartum weight. The program provides support, education, and resources via text messages/web for activities already being done. LA MOMs goes to them via their mobile phone/tablet/or internet.